PENDAMPINGAN PEMBUATAN 4D BOOK UNTUK MENINGKATKAN SOFTSKILL MAHASISWA ASRAMA UNIVERSITAS NEGERI MALANG - Khotimah, Khusnul; Untari, Esti; Ahdianto, Erif (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
One technology that is developing rapidly now is Augmented Reality (AR) technology. AR is a technology that combines/combines the virtual world with the real world by projecting virtual objects in real-time reality. This means that AR is a technology that can display information from the virtual world into the real world via smartphones, webcams, cameras, computers, or special glasses. Referring to the description above, AR can be integrated into learning activities, especially in making teaching materials or books for students. With current developments in technology, it is necessary to digitize teaching materials or books by integrating AR technology. Universitas Negeri Malang (UM) is a state university in the city of Malang whose output is to produce/produce professional prospective educators (teachers). One of the facilities provided by the UM campus is student dormitories. The dormitory residents at Campus 2 of the UM tend to be students studying primary school teacher education (PGSD). As a prospective teacher, especially a prospective elementary school teacher, of course you need to develop your soft skills that can support your profession as a prospective teacher. As a prospective teacher, of course, you are expected to be able to always be adaptive to developments over time and increasingly sophisticated technology. Therefore, as campus residents within the UM student dormitory, it is necessary to provide assistance to improve soft skills that have not been accommodated/facilitated in lectures. One of the soft skills needed to become a teacher who is adaptive to technological developments is assisting in making books or teaching materials that integrate AR-4D.